Beneficios de implementar un clúster de bases de datos Oracle en los servicios críticos de las tecnologías de información - Riccio Chávez, Francisco Martín (2015)
This scientifi c article provides a general knowledge about the infrastructure of a clustering Oracle databases, which highlights the primary benefi ts for companies that offer critical services within the information technology (IT) realm, via a justifi ed investment. For a better understanding, the makeup of this technology will be explained. Various research examples and implementations will also be illustrated, on-premises and off -premises, by the students of the university. It should be noted that this research will be focused on the Oracle Real Application Cluster (RAC) and Oracle Flex Cluster. The final subject is a new feature that provides the Oracle database, which references 12c version technology, with the current date being the same date this article was written.